2019
DOI: 10.1111/jfbc.12774
|View full text |Cite
|
Sign up to set email alerts
|

Cyanidin and cyanidin-3-glucoside derived from Vigna unguiculata act as noncompetitive inhibitors of pancreatic lipase

Abstract: The consumption of legumes positively correlated with the reduction of body weight. In the present study, we identified and evaluated pancreatic lipase inhibitors from Vigna unguiculata and unraveled their mode of inhibition. The highly sensitive fluorometric method was adopted to access the pancreatic lipase activity and the ethanolic extract of Vigna unguiculata showed the maximum inhibition (IC50 of 15.2 µg/ml). Cyanidin and cyanidin‐3‐glucoside are the major anthocyanins observed in Vigna unguiculata. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 51 publications
1
15
0
1
Order By: Relevance
“…The water solubility properties of the phenolic compounds could enhance their interactions with target enzymes within the hydrophilic environment of the gastrointestinal tract. For example, the aqueous extracts of some bean varieties were shown to have stronger lipase inhibition than the ethanolic extracts [ 28 ]. Inhibition of α-amylase was mainly dose-dependent except for brinjal and stem amaranth, where their decreases occurred at higher sample concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The water solubility properties of the phenolic compounds could enhance their interactions with target enzymes within the hydrophilic environment of the gastrointestinal tract. For example, the aqueous extracts of some bean varieties were shown to have stronger lipase inhibition than the ethanolic extracts [ 28 ]. Inhibition of α-amylase was mainly dose-dependent except for brinjal and stem amaranth, where their decreases occurred at higher sample concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Lipase is secreted in the pancreas and is used as a catalyst to aid triglyceride hydrolysis in the stomach, and this hydrolysis is completed by intestinal lipase in the small intestine [ 28 , 37 ]. It has been estimated that about 50–70% of total dietary fats are hydrolyzed for absorption by PL [ 38 ], which emphasizes the importance of this enzyme in calorie release from diets.…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic lipase enzyme is required for the dietary fat absorption. Therefore, it is important to inhibit pancreatic lipase enzyme in order to reduce obesity development (Vijayaraj et al, 2019). Anthocyanin-rich fruits and vegetables contain significant anthocyanins that are able to inhibit pancreatic lipase enzyme, thus, some fruits and vegetables rich in anthocyanins have significant effects on preventing obesity.…”
Section: Inhibition Of Pancreatic Lipase Enzymementioning
confidence: 99%
“…In the research in which the effect of litchi flower extract in the Mediterranean diet containing anthocyanin-rich fruit and vegetables was investigated, it was determined that the extract samples have a suppressive effect on pancreatic lipase. In the researches in which some anthocyanin-containing fruits were used, it was found that pomegranate and blood orange juices have significant pancreatic lipase inhibition due to the high anthocyanin content (Chen et al, 2018;Xie et al, 2018;Vijayaraj et al, 2019). In another research, black rice extract containing cyanidin 3-glucoside and peonidin 3-glucoside anthocyanins in the arrest of cholesterol absorption in Caco-2 cells has been tested.…”
Section: Inhibition Of Pancreatic Lipase Enzymementioning
confidence: 99%
“…Moreover, anthocyanins treatment improved insulin sensitivity and suppressed the comorbidities of obesity in vitro [ 83 ]. Cyanidin and C3G-rich ethanolic extract of Vigna unguiculata showed significant pancreatic lipase inhibition in vitro, which indicated that V. unguiculata anthocyanins have anti-obesity potential [ 84 ] ( Table 3 ).…”
Section: Anthocyanins and Obesitymentioning
confidence: 99%